(untitled) (Comprehensive Journal of Science, 2025)
Bananas are a rich source of potassium, which naturally contains trace amounts of the radioactive isotope potassium-40. This study investigates the levels of radioactive potassium40 in bananas supplied to the Libyan market, with a focus on samples imported from Costa Rica and Ecuador. Fifteen banana samples were collected, prepared, and analyzed using gamma spectrometry with a high-purity germanium (HPGe) detector. The activity concentrations of K⁴⁰ were found to range between 93.8±3.3 and 276.9±10.2 Bq/kg, with Costa Rican bananas exhibiting higher average concentrations (226.25±8.8 Bq/kg) compared to Ecuadorian bananas (186.85±8.25 Bq/kg). The results indicate that while the levels of K⁴⁰ in bananas are within safe limits, variations in concentrations may be influenced by geographical and agricultural factors, such as soil composition and the use of potassium-rich fertilizers. The study highlights the importance of monitoring radioactivity in food, particularly in regions with limited radiological data, and contributes to the global understanding of radiological risks associated with food consumption. The findings underscore the need for further research into the factors affecting radionuclide uptake in crops